Association of adiponectin polymorphisms with the risk of diabetic nephropathy in type 2 diabetes: A meta‐analysis 脂联素基因多态性与2型糖尿病肾病的相关性：一项meta分析. (15th July 2014) - Cai, Yuli; Zeng, Tianshu; Chen, Lulu
Abstract: Objective: Adiponectin gene polymorphisms have been reported to be associated with the risk of diabetic nephropathy (DN) in type 2 diabetes mellitus (T2DM) patients. However, the results are inconsistent. Methods: Electronic literature databases and reference lists of relevant articles published until December 2013 were searched as part of a systematic review and meta‐analysis to clarify the association between adiponectin gene polymorphisms and DN susceptibility in T2DM. Fixed‐ or random‐effects models were used to calculate the effect sizes of odds ratio (OR) and 95% confidence intervals (95%CI). Results: Eleven case control studies were included. Overall, a significant association was observed for rs2241766T/G polymorphisms under the recessive model (GG vs TT+TG: OR 1.75; 95% CI 1.09–2.80; P  = 0.02). For rs17300539G/A, a significant association was observed under the GA vs GG model (OR 1.74; 95% CI 1.13–2.68; P  = 0.01) and A vs G allele model OR 1.65; 95% CI 1.13–2.41; P  = 0.009). After stratification by ethnicity, we found that the rs2241766 T/G dominant model (GG+TG vs TT: OR 1.52; 95% CI 1.12–2.07; P  = 0.007), heterozygous model (TG vs TT: OR 1.52; 95% CI 1.01–2.27; P  = 0.04) and G vs T allele (OR 1.50; 95% CI 1.07–2.10; P  = 0.02) may be associated with DN risk in the Caucasian population. For rs17300593G/A, the dominant model (GA+AA vs GG: OR 1.75; 95% CI 1.15–2.67; P  = 0.009) may be associated with DN risk in the Caucasian population. Conclusion: Adiponectin rs2241766T/G and rs17300593G/A rather than rs1501299G/T and rs266729C/G polymorphisms were associated with the risk of DN in T2DM, especially in the Caucasian population. 摘要: 目的： 有研究报道了脂联素基因多态性与2型糖尿病患者的糖尿病肾病风险相关。然而，这些报道的结果并不一致。 方法： 通过计算机全面检索发表于2013年12月之前关于脂联素基因多态性与2型糖尿病肾病的相关性的研究，追溯其参考文献，并据此进行系统性回顾和meta分析，以阐明脂联素基因多态性与2型糖尿病患者的糖尿病肾病易感性之间的关系。使用固定或随机效应模型计算效应值的比值比（OR）和95%可信区间（95% CI）。 结果： 共纳入了11项病例对照研究。总体来说，在隐形遗传模型下脂联素基因rs2241766T/G多态性位点具有显著的相关性，GG基因型携带者患糖尿病肾病的风险与TT+TG基因型携带者的差异有统计学意义（OR：1.75；95% CI：1.09‐2.80； P  = 0.02）。在脂联素基因rs17300539G/A位点，以共显性模型计算，GA基因型携带者和GG基因型携带者的糖尿病肾病易感性有显著性差异（OR：1.74；95% CI：1.13‐2.68； P  = 0.01）；在等位模型中，等位基因A引起糖尿病肾病风险明显高于等位基因G（OR：1.65；95% CI：1.13‐2.41； P  = 0.009）。基于人种的亚组分析显示，脂联素基因rs2241766 T/G多态性可增加高加索人群患2型糖尿病肾病的风险：无论是在显性遗传模型（GG+TG vs TT：OR：1.52；95% CI：1.12–2.07）； P  = 0.007），共显性模型（TG vs TT：OR：1.52；95% CI：1.01–2.27； P  = 0.04），还是等位模型（G vs T：OR：1.50；95% CI：1.07–2.10； P  = 0.02）。以显性遗传模型计算，在脂联素基因rs17300593G/A多态性位点，高加索人群GA+AA基因型携带者患2型糖尿病肾病的风险明显高于GG基因型携带者（OR：1.75；95% CI：1.15–2.67； P  = 0.009）。 结论： 脂联素基因rs2241766T/G和rs17300593G/A而不是rs1501299G/T 和rs266729C/G多态性位点与2型糖尿病的糖尿病肾病风险具有相关性，且在高加索人群中尤为明显。